Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Prerequisites - p.4 - Factoring Polynomials - Exercises - Page 39: 62



Work Step by Step

Use: $6x=4x+2x$ and $-6x=-4x-2x$ $(x^2+8)^2-36x^2=(x^2+8)^2-(6x)^2=(x^2+8+6x)(x^2+8-6x)=(x^2+4x+2x+8)(x^2-4x-2x+8)=[x(x+4)+2(x+4)][x(x-4)-2(x-4)]=(x+2)(x+4)(x-2)(x-4)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.